Hubungan Karakteristik Balita, Sosial Ekonomi, dan Ketahanan Pangan Rumah Tangga dengan Stunting di Kampung 1001 Malam Surabaya, Surabaya - Evita Hasana Putri; Lailatul Muniroh (Universitas Airlangga, 2023)
Background: Stunting is a chronic nutritional deficiency condition defined by low-height for age. This condition is caused by various factors such as food intake, infectious diseases, food security conditions, parenting patterns, economy and environmental health conditions. Objective: The purpose of this study was to determine the relationship between the characteristics of toddlers, socioeconomic and household food security with stunting nutritional status in toddlers aged 12 – 59 months in Kampung 1001 Malam Surabaya, Surabaya. Methods: This research was a quantitative with a cross sectional study design. The sample in this study was amounted to 35 children under five with sampling technique was total sampling. The independent variables in this studi were the characteristics of children under five, socioeconomic, and household food security, while the dependent variabel is stunting condition. Data collection method used secondary data for birth weight and height of toddlers, for primary data such as maternal education, mother's occupation, family income, and household food security. Data analysis using chi square and Rho spearman. Confidence interval for this study is 95%. Results: The results showed that 57.1% of children were female, 77.1% aged over 24 months, 8.6% had a history of low birth weight, 28.6% had a history of underweight, 62.9% of mothers had low education, 94.2% work as housewives, 57.1% have an income of >Rp. 500,000 – Rp. 1,000,000, 80% have food insecure and 40% of children under five are stunted. Analysis of the test showed that there was no relationship between the characteristics of toddlres (birth weight (p=0.704) and birth length (p=0.729), socioeconomic (mother's education (p=0.116), mother's occupation (p=0.338), and family income. (p=0.540; rs=-0.107) and food security (p=0.863) with stunting in toddlers. Conclusion: In conclusion, characteristics of toodlers, socio-economic and household food security are not risk factor of stunting.